Synthesis of α-alumina developed from waste aluminium using precipitation technique - Aiman A., Mokaizh; Jun Haslinda, Shariffuddin (IOP Publishing, 2021)
The heated aluminium containers were added to a solution of 8.0 M H2SO4 solution, which eventually yielded a solution of Al2(SO4)3 after a series of stepwise precipitation reactions. Al2(SO4)3 was presented in large quantities of H2SO4 in the white semi-fluid solution; there were some unreacted aluminium parts. The solution was subjected to filtration and then mixed with anion in a ratio of 2:3, this resulted in the formation of a white layer Al2(SO4)3•18H2O. Thereafter, Al2(SO4)3•18H2O was calcined in an electric oven for 2 h at various calcination temperatures (500, 700, 900, 1100, and 1300°C). The mixtures were heated and cooled at a rate of 10°C/min. XRD was employed to investigate variations in temperature and determination of elemental accumulation of alumina produced. Ah(SO4)3•18H2O was due to a series of aluminium compositions produced from dehydration. All transitions from low temperatures to aluminium phases were converted to high-temperature α-Al2O3. The results obtained from X-ray disintegration showed that the α-Al2O3 phase was obtained at a reaction temperature of about 1150°C and above.